Asosiasi Mega Gastropoda Pada Padang Lamun Monospesifik Pulau Badak Badak, Kota Bontang - Marsellinda Setiance Putri Batuallo; Aditya Irawan; Lily Inderia Sari (Universitas Mataram, 2024)
Mega Gastropods play an important role in the food chain in bottom waters. Mega Gastropods are associated with seagrass beds which have sand and sandy mud bottom substrates. The aim of the research is to determine the association of Mega Gastropods in monospecific seagrass beds as their habitat. This research was carried out from October 2023 - February 2024 in the seagrass beds of Badak Badak Island. The station is divided into 3 stations and each station is divided into 3 zones. Seagrass and Mega Gastropod samples were taken using a 50x50cm quadrant frame. The relationship between seagrass density and Mega Gastropod density was used by the Pearson's Product Moment correlation test and the distribution of basic substrate fractions and the distribution of Mega Gastropod species was used by Principal Component Analysis (PCA) and Corespondence Analysis (CA). The Mega Gastropods found consisted of L. turturella, C. tigris, P aluco, and T. telescopium. The relationship between Mega Gastropod density and E. acoroides density was not positively correlated and the presence of Mega Gastropod species was associated with the characteristics of the basic substrate fraction.